Managing upward and downward through informal networks in Jordan: the contested terrain of performance management - Melhem, Muntaser J.; Darwish, Tamer K.; Wood, Geoffrey; Abushaikha, Ismail (Wiley, 2024)
This study explores how local managers, in practicing Human Resource management (HRM), may pursue their own interests that are out of line with the agendas of headquarters in multinational companies (MNCs). It is widely acknowledged that informal networks have an impact on HRM practices in emerging markets. While these networks are often regarded as beneficial for organizations in compensating for institutional shortfalls, they may also lead to corruption, nepotism, or other ethical transgressions. Indigenous scholarship on informal networks in emerging markets has highlighted how their impact occurs through a dynamic process; powerful placeholders deploy informal networks to entrench existing power and authority relations when managing people. Qualitative data were gathered through 43 in-depth interviews and documentary evidence from MNCs operating in Jordan. MNCs are subject to both home and host country effects; we highlight how, in practicing HRM, country of domicile managers deploy the cultural scripts of wasta informal network to secure and enhance their own relative authority. HRM practices are repurposed by actors who secure and consolidate their power through wasta. They dispense patronage to insiders and marginalize outsiders; the latter includes not only more vulnerable local employees but also expatriates. This phenomenon becomes particularly evident during the performance appraisal process, which may serve as a basis for the differential treatment and rewards of employees. Consequently, this further dilutes the capacity of MNCs to implement—as adverse to espousing—centrally decided approaches to HRM.
Keywords: employee voice; expatriates; host country effects; informal networks; institutional logics; MiddleEast; MNCs; performance appraisals